Komposisi Probiotik Yang Berbeda Pada Media Green Water System (GWS) Untuk Peningkatan Kelangsungan Hidup dan Pertumbuhan Benih Ikan Lele(Clarias sp.) - Suparmin, Suparmin; Shilmana, M. Idham; Salim, Ridwan (Jurnal Kelautan, Lingkungan, dan Perikanan, 2024)
New technology in catfish farming is starting to be used, one of which is the use of probiotics in GWS (Green Water System) fish farming. This research aims to provide information to fish farmers regarding the appropriate and appropriate use of probiotics in cultivating catfish (Clarias sp.) using the Green Water System (GWS) method. The design used was three treatments and three replications, namely 1) treatment of bacterial yeast composition, lactic acid and probiotics, basillus subillis, basillus megaterium, basillus polimyxa; 2) probiotic treatment of fish salt, molasses, dolomite lime, and probiotic lactobacillus casei, saccharomyces cerevisiae; and 3) probiotic treatment of dolomite lime, probiotic saccharomyces cerevisiae, lactobacillus acidophilus, bacillus subtilis. The research results showed that the addition of probiotics in composition 1 was the best formulation in the green water system water media for fish survival rate, namely 91.41%, daily weight growth, namely 0.91 grams per day, and feed conversion ratio value, namely 1.18. The results of measuring water quality parameters obtained from treatment 1 provided high growth of plankton and bacteria in the GWS water media. In general, the water quality parameters in the three treatments showed an optimum range for DO parameters of 5.5 - 6 ppm, temperature 28 - 28.6 0C, and pH 6.5.